Business Responsability for Environmental protection in developing countries: Report of the International Worshop Heredia, Costa Rica, 22-24 Septiembre 1997 - United Nations Research Institute for social Development ( UNRISD) - Universidad Nacional (UNA) (Nicaragua: UNRISD-UNA, 1998)
Tratar sobre la responsabilidad de las empresas en la protección del medio ambiente en países en desarrollo.
1. Tendencias y perspectivas 2. Estartegia y tácticas
incluye índice
Col. Admón
Keywords: 1. WELCOMING ADDRRESSES 2. PAPER ABSTRACTS AND SUMMARIES